Earthquake Response of RC Infilled Frame with Wall Openings in Low-rise Hotel Buildings. (2015) - Sukrawa, Made
Abstract: To study the earthquake response of RC infilled frame structures with variable wall opening, 3-D computer models were made for 3, 4, and 5 storey typical hotel buildings consisting of six frames of 3 bays. In X-direction, the middle bay was open and the side bays were in-filled with full (solid) walls. In Y-direction, the interior walls consisted of door opening in the corner and the exterior walls consisted of window openings with variable ratios of 20%, 40%, 60%, 80%, and 100%. Prior to modeling the 3-D structure, 2-D validation models using diagonal strut and shell element were made based on test results of simple infilled frames with various openings. For the strut model, the wall with opening was modeled using diagonal strut of reduced width. For the shell element model the wall was modeled as is with gap element at the interface between the frames and the wall. Considering crack development and non linear stress-strain relationship of the materials, the lateral load-displacement diagrams of the shell element models fit the test result better than the strut ones. Models with lintels around the wall openings were also created for validation and the results show that lintels stiffen the frame and strengthen the wall around the openings. The shell element model was then used to create 3-D models of the hotel building with lintels around the wall openings. Analysis and design of the 3-D models show that the earthquake responses of RC frames infilled with walls of opening ratios 20% to 60% are significantly stiffer and stronger than that without infill wall. However, the contribution of infill walls with 80% opening in reducing storey drift and frame reinforcement was much smaller. Accordingly, the infill walls with opening ratios of less than 80% should be considered in the structural modeling to obtain a more accurate analysis and efficient design.